More credo, less capes: Why and how we should use comics in the Religious Education classroom. Issue 1 (1st July 2015) - Hancock, Rae
Research into religion and comics is flourishing and has called attention to the various ways in which religion features across the medium. However, consideration has not yet been given to the role of comics with religious dimensions in the Religious Education (RE) classroom despite significant attention having been paid to their use in schools through subjects such as English. Nonetheless comics are being used outside the classroom to communicate religious ideas and references to the medium are beginning to appear on exam specifications with the intention that candidates engage with religious representations in the media and popular culture. As such, seeking ways to bring comics with religious dimensions into a subject that concerns itself with 'learning about' and 'learning from' religion allows comic scholarship the potential to be genuinely impactful. A compulsory subject without a strict, prescriptive curriculum, RE is at once accused of indoctrination and called upon to be at the forefront of the battle against extremism. This article presents an overview of the contemporary RE climate in English state secondary schools, then builds on the rationale of why we should use more comics in RE and suggests approaches to using selected comics. The examples considered are necessarily broader than those typically discussed by scholars as they are chosen based on their pedagogical appropriateness. Consideration is given to the theoretical and practical challenges facing the rationale and it is concluded that in order to continue to explore, refine and validate the usefulness of comics in RE the body of sources used needs to expand and become representative in its breadth. Further, continuing to examine why and how we should use comics in the classroom has the potential to deepen and improve the quality of RE and provide comics scholarship opportunities to examine practical applications of the medium.